University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 8 - Section 8.1 - Integration by Parts - Exercises - Page 429: 71



Work Step by Step

$$A=\int\sin^{-1}xdx$$ Take $y=f^{-1}(x)=\sin^{-1}x$ So $x=f(y)=\sin y$ Applying the formula $\int f^{-1}(x)dx=xf^{-1}x-\int f(y)dy$, we have $$A=x\sin^{-1}x-\int\sin ydy$$ $$A=x\sin^{-1}x-(-\cos y)+C$$ $$A=x\sin^{-1}x+\cos y+C$$ $$A=x\sin^{-1}x+\cos(\sin^{-1}x)+C$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.